KEMAMPUAN MENULIS TEKS ULASAN NOVEL SANG PEMIMPI KARYA ANDREA HIRATA SISWA KELAS VIII SMP NEGERI 1 SUNGAI APIT - Zulfahmi '; Auzar '; Dudung Burhanudin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study discussed one of literary creation that is novel. Novel studied was Andrea Hirata’s novels, entitled Sang Pemimpi. In this study, the formulation of the problem is how the level of student’s ability in write a review text of novel Sang Pemimpi by Andrea Hirata that are divided into the orientation, interpretation, evaluation, and summary. The study that aim to find out the level of student’s ability in write a review text used descriptive methods with statistical techniques. In this study found that the mean value of student's ability of grade VIII at SMPN 1 Sungai Apit in write review text is 78.72. This result also indicated that among the four parts of the review text, the structure that has improved is evaluation structure, while that has not been a good improvement was the summary.Key words: Novel, structure, review text.